Depression among Women with Primary Infertility attending an Infertility Clinic in Riyadh, Kingdom of Saudi Arabia: Rate, Severity, and Contributing Factors - Al-Homaidan, Dr. Homaidan Turki (International Journal of Health Sciences, 2011)
Background: Infertility is a severely distressing experience for many couples. Depression is considered as one of the main psychological disorders associated with infertility and it may significantly affect the life of infertile individuals, their treatment, and follow-up. Objective: The objective of the study was to determining the prevalence and predisposing factors of depressive disorders among the infertile compared to fertile women. Methodology: Rate of depression was explored by this cross-sectional study carried out among women attending In-Vitro Fertilization Clinic (91 infertile women) and Well Baby Clinic (94 fertile women) at King Abdulaziz Medical City (KAMC) in Riyadh, KSA. Self administrated questionnaire including Beck Depression Inventory (BDI) was used.Â  Mean BDI score was measured and its relation with different variables was explored, such as age, educational level, duration of infertility, pressure from family members, miscarriages and support from husband. Results: This study showed that 49 (53.8%) of the infertile women and 35 (37.2%) of the fertile women had depression. Mean BDI score between infertile and fertile women was significantly different (p <0.001). Infertile women were found to be more severely depressed (p =0.014). Among the infertile women, those who had pressure from family members for not getting pregnant were more depressed than those with no such pressure (P=0.001). Conclusion: Depression is more common and severe in infertile women than fertile women. Pressure from family to get pregnant is a significant contributor to depression. Caregivers should routinely screen infertile women for depression during and after treatment for infertility and manage concomitantly. Key Words: Depression, Infertility